Small molecule purine and pseudopurine derivatives: synthesis, cytostatic evaluations and investigation of growth inhibitory effect in non-small cell lung cancer A549 - Andrea Bistrović; Petra Grbčić; Anja Harej; Mirela Sedić; Sandra Kraljević-Pavelić; Sanja Koštrun; Janez Plavec; Damjan Makuc; Silvana Raić-Malić (Taylor & Francis Group, 2018)
Novel halogenated purines and pseudopurines with diverse aryl-substituted 1,2,3-triazoles were prepared. While p-(trifluoromethyl)-substituted 1,2,3-triazole in N-9 alkylated purine and 3-deazapurine was critical for strong albeit unselective activity on pancreatic adenocarcinoma cells CFPAC-1,1-(p-fluorophenyl)-1,2,3-triazole derivative of 7-deazapurine showed selective cytostatic effect on metastatic colon cancer cells SW620. Importantly, 1-(p-chlorophenyl)-1,2,3-triazole-tagged benzimidazole displayed the most pronounced and highly selective inhibitory effect in nM range on non-small cell lung cancer A549. This compound revealed to target molecular processes at the extracellular side and inside the plasma membrane regulated by GPLD1 and growth factor receptors PDGFR and IGF-1R leading to the inhibition of cell proliferation and induction of apoptosis mediated by p38 MAP kinase and NF-κB, respectively. Further optimisation of this compound as to reduce its toxicity in normal cells may lead to the development of novel agent effective against lung cancer.